2012
DOI: 10.3109/02713683.2012.725797
|View full text |Cite
|
Sign up to set email alerts
|

Na+/K+-ATPase Expression Changes in the Rabbit Lacrimal Glands During Pregnancy

Abstract: Purpose To investigate the expressional changes of Na+/K+-ATPase subunits in the lacrimal glands (LG) of term pregnant rabbits. Methods LG were obtained from term pregnant rabbits and age-matched female control rabbits for laser capture microdissection (LCM), real time RT-PCR, western blot, and immunofluorescence. The mRNA and proteins of α1, α2, β1, β2, and β3 subunits of Na+/K+-ATPase were detected and quantified. Results Although only the mRNA for β3 from whole LG of pregnant rabbits was significantly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…However, lachrymal gland dysfunction would appear to be consequent to changes in Na(+)/K(+)-ATPase subunits and alterations of aquaporin AQP4 and AQP5 expression in gland acini, rather than to a hormonal influence, as shown in animal models. 53,54 …”
Section: The ''His and Hers'' Ocular Surfacementioning
confidence: 98%
“…However, lachrymal gland dysfunction would appear to be consequent to changes in Na(+)/K(+)-ATPase subunits and alterations of aquaporin AQP4 and AQP5 expression in gland acini, rather than to a hormonal influence, as shown in animal models. 53,54 …”
Section: The ''His and Hers'' Ocular Surfacementioning
confidence: 98%
“…Conversely, for pregnant women in the third trimester, dry eye symptoms are caused by high estrogen and progesterone levels ( 58 ). Estrogen therapy for dry eye is controversial; for menopausal women, randomized controlled trials have shown that ATs combined with estradiol eye drops are more effective than ATs alone ( 59 ). Coksuer et al ( 60 ) showed that postmenopausal women continued to take drospirenone 2 mg + estradiol 1 mg for six months, BUT and Schimer trial results improved.…”
Section: Common Dry Eye Factorsmentioning
confidence: 99%
“…[ 134 ] NKA expression was observed in meibomian and lacrimal glands in animal studies. [ 83 , 82 ] A study observed that the expression of NKA remained unaltered in ocular surface tissue in a DED animal model. [ 78 ] Interestingly, a reduction in the expression of NKA was observed in aged meibomian glands and periplocin, and NKA agonist was reported to increase NKA expression and promote proliferation of meibocytes in mice.…”
Section: Other Ion Channelsmentioning
confidence: 99%